1998
DOI: 10.1542/peds.102.5.e60
|View full text |Cite
|
Sign up to set email alerts
|

Muscularity and Fatness of Infants and Young Children Born Small- or Large-for-Gestational-Age

Abstract: SGA infants remain smaller and LGA infants larger in size through early childhood, but the discrepancies in weight are primarily attributable to differences in lean body mass (muscularity). Fatness is less affected. Thus, based on the fatness indicators used, at any given weight for infants and children 2 to 47 months of age, percent body fat appears to be relatively higher for children who were SGA at birth and lower in those who were LGA at birth. These differences in body composition for SGA infants support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
177
1
12

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(197 citation statements)
references
References 26 publications
7
177
1
12
Order By: Relevance
“…Those studies that have done so have confirmed the general association between birth weight and later lean mass but have shown weak or nonsignificant associations with later fatness (Hediger et al 1998;Kensara et al 2005;Sachdev et al 2005;. One study (Kensara et al 2005) has reported an increased percentage fat in low-birth-weight elderly adults after adjusting for adult BMI, consistent with several others reporting a general inverse association between birth weight and later fatness (Table 1).…”
Section: Fetal Growth and Later Body Compositionmentioning
confidence: 52%
“…Those studies that have done so have confirmed the general association between birth weight and later lean mass but have shown weak or nonsignificant associations with later fatness (Hediger et al 1998;Kensara et al 2005;Sachdev et al 2005;. One study (Kensara et al 2005) has reported an increased percentage fat in low-birth-weight elderly adults after adjusting for adult BMI, consistent with several others reporting a general inverse association between birth weight and later fatness (Table 1).…”
Section: Fetal Growth and Later Body Compositionmentioning
confidence: 52%
“…35,36 This growth acceleration in childhood can lead to a disproportionately high-fat mass in relation to lean body mass. 37 These effects on body composition may favor the development of cardiovascular disease later in life. 38,39 The underlying mechanisms as well as the critical periods of weight gain that contribute to later disease are still debated.…”
Section: Discussionmentioning
confidence: 99%
“…Two largescale studies support the view that SGA infants remain smaller through early childhood. 17,18 However, TF was not available during either study. Our findings suggest that the growth of SGA infants provided high-nutrient formula may be potentiated.…”
Section: Discussionmentioning
confidence: 99%